Comparative Study of Nutritional Content and Amino Acid Profile on Rono Poso Fish (Adrianichthys oophorus) and Rono Lindu Fish (Oryzias sarasinorum) Endemic of Central Sulawesi - Jamaluddin Jamaluddin; Meita Meita; Syariful Anam; Agustinus Widodo; Pitriani Pitriani (Pharmaceutical Reports, 2022)
Rono Poso fish (Adrianichthys oophorus) originating from Lake Poso and  Rono Lindu fish (Oryzias sarasinorum) from Lake Lindu, is central Sulawesi endemic fish that consumed the communities around the lake, but it is not known nutritional content. This study aims to determine the nutrient content and amino acid profile in Rono Poso and Rono fish Lindu. Ash content analysis testing using the dry ashing method, testing the moisture content using the oven method, using soxhlet fat, and protein content using the method and the testing Kjeldhal amino acid profile using Chromatography Hight Performance Liquid (HPLC). The results showed that several nutrients and amino acid profiles differ between the two samples. In Rono Poso fish containing ash 11:00%, water 6:11%, 58.88% protein,  fat, and carbohydrates 22.68% 1:33%. In Rono Lindu containing ash 18.84%, water 9.77%, 58.97% protein, fat, and carbohydrate 10:35% 2:07%.